Lebanese Higher Education and the Labor Market: A Marriage or a Divorce? - Youssef, Leila (International Higher Education, 2025)
Lebanon suffers from political stagnation, social discontent, and economic collapse. Mismatch between educational choices and labor market needs persists, causing brain drain and high unemployment among university graduates. With a service-oriented market, primarily small and medium enterprises with low job creation prospects, and employer dissatisfaction with university graduates’ skills, the situation for graduates is difficult. This article aims to assess the link between higher education and the labor market amid political and economic instability.